Regularity of Radial Solutions to the Complex Hessian Equations (Journal of Partial Differential Equations, 2010)
In this paper we consider regularities of radial solutions to the degenerate complex Hessian equations. Our results generalize some results for Monge-Ampere equation in [Monn, Math. Ana. 275 (1986), pp. 501-511] and [Delanoe, J. Diff. Eqn. 58 (1985), pp. 318-344].
Keywords: The complex Hessian equation; regularity